Experimental dosimetric comparison of 1H, 4He, 12C and 16O scanned ion beams. (13th April 2017) - Tessonnier, T; Mairani, A; Brons, S; Haberer, T; Debus, J; Parodi, K
Abstract: At the Heidelberg Ion Beam Therapy Center, scanned helium and oxygen ion beams are available in addition to the clinically used protons and carbon ions for physical and biological experiments. In this work, a study of the basic dosimetric features of the different ions is performed in the entire therapeutic energy range. Depth dose distributions are investigated for pencil-like beam irradiation, with and without a modulating ripple filter, focusing on the extraction of key Bragg curve parameters, such as the range, the peak-width and the distal 80%–20% fall-off. Pencil-beam lateral profiles are measured at different depths in water, and parameterized with multiple Gaussian functions. A more complex situation of an extended treatment field is analyzed through a physically optimized spread-out Bragg peak, delivered with beam scanning. The experimental results of this physical beam characterization indicate that helium ions could afford a more conformal treatment and in turn, increased tumor control. This is mainly due to a smaller lateral scattering than with protons, leading to better lateral and distal fall-off, as well as a lower fragmentation tail compared to carbon and oxygen ions. Moreover, the dosimetric dataset can be used directly for comparison with results from analytical dose engines or Monte Carlo codes. Specifically, it was used at the Heidelberg Ion Beam Therapy Center to generate a new input database for a research analytical treatment planning system, as well as for validation of a general purpose Monte Carlo program, in order to lay the groundwork for biological experiments and further patient planning studies.